Interventions for increasing return to sport rates after an anterior cruciate ligament reconstruction surgery: A systematic review - Drole, Kristina; Paravlic, Armin H. (Frontiers in Psychology, 2022)
Background: An injury followed by surgery poses many challenges to an athlete, one of which is rehabilitation, with the goal of returning to sport. While total restoration of physical abilities is a primary goal for most athletes, psychosocial factors also play a role in the success of an athlete’s return to sport. The purpose of this review was to examine the effectiveness of exercise and psychosocial interventions on return to sport (RTS) rates, which might be one of the most important outcomes for elite athletes. Methods: To carry out this review, PubMed, SAGE Journals, Web of Science, SPORTDiscus, ScienceDirect and Google Scholar databases were searched from inception to July 2022. The inclusion criteria consisted exercise or psychosocial intervention for athletes after ACLR, with reporting RTS rates as an outcome. Results: From 1032 identified articles, four reports (N=130) met inclusion criteria, all of which examined the recovery after anterior cruciate ligament reconstruction. The mean MINORS score for the included studies was 16.3 ± 6.1, of which non-comparative studies scored 11.0 ± 1.4, while comparative studies scored 21.5 ± 0.7. There were consistent findings for benefits of exercise and psychosocial interventions on RTS rates. Return to preinjury rates in the reviewed studies vary between 63-95% with lower % observed in female athletes and with shorter follow-up. Interventional studies reporting RTS rates with a larger sample size and longer follow-up are needed. Conclusion: Physical and psychological function, as well as social support can be influenced by appropriate interventions, indicating future work on rehabilitation programs for return to preinjury might consider taking the holistic approach addressing those.